PEMBERIAN NATRIUM BENZOAT TERHADAP KUALITAS DAN DAYA SIMPAN SIRUP JAMBU METE - Naema Bora (Politeknik Pertanian Negeri Kupang, 2008)
Effect of Benzoic Acid Supplement to Storage and Quality of Syrup of Jambu Mete. The research was executed at laboratory of THP Politani Negeri Kupang, from August to November 2006. This research aimed to carry out influence of benzoic acid supplement to quality of syrup jambu tee during storage. This research used completely randomized design (RAL). The treatments studied were concentration of benzoic acid by 5 levels, that is 0 mg/liter syrup (control), 200 magnesium /liter syrup, 400 mg/liter syrup, 600 mg/liter syrup and 800 mg/liter syrup. Variables observed covered number of microbe colonies, sour total and test hedonic, what observed from 0 month of until 2 month of storage. Statistical analysis showed that concentration of benzoic acid significantly affected to quality of syrup jambu mete during storage. benzoic acid concentration of 600 mg/liter syrup performed best quality of syrup (safe to be consumed) compared to other treatments.Key word: Natrium benzoate, storage, quality syrup, jambu mete.